Endodontic management of traumatized permanent teeth: a comprehensive review. (31st March 2021) - Krastl, G.; Weiger, R.; Filippi, A.; Van Waes, H.; Ebeleseder, K.; Ree, M.; Connert, T.; Widbiller, M.; Tjäderhane, L.; Dummer, P. M. H.; Galler, K.
Abstract: The pulp plays a key role in the treatment of traumatic dental injuries (TDIs) and is strongly associated with the outcome, particularly in severe cases. A correct pulp diagnosis is essential as it forms the basis for developing the appropriate management strategy. However, many TDIs are complex, and their treatment requires a profound knowledge of the physiological and pathological responses of the affected tissues. This comprehensive review will look at the dentine–pulp complex and its interaction with the surrounding tissues following TDIs. The literature up to 2020 was reviewed based on several searches on PubMed and the Cochrane Library using relevant terms. In addition to the recently revised guidelines of the International Association of Dental Traumatology, this article aims to provide background information with a focus on endodontic aspects and to gather evidence on which a clinician can make decisions on the choice of the appropriate endodontic approach for traumatized permanent teeth.